In vitro Androgenesis of Some Wheat (Triticum aestivum L.) Varieties and their F1, F2 Progenies and Combining Ability of Embryoid Production - Hasan, M; Pauk, J; Kertesz, Z (Progressive Agriculture, 2014)
Six parental lines along with their F1 and F2 progenies were investigated for general combining ability (GCA) effects on embryo-like-structure (ELS) production in anther culture. Significant differences were found among the parents in respect to the ELS production. Evaluating the combining ability effects, among the female parents Alfold showed the best result in ELS production, while Palma was the best among the male lines. While comparing F1 and F2 generations, in most of the cases (except one) F2 generation was superior in ELS production. Polygenic effect plays a key role in such type of superiority in the F2 generation. The reason for such superiority may be due to the recombination of superior genes. DOI: http://dx.doi.org/10.3329/pa.v18i2.18091 Progress. Agric. 18(2): 57 - 60, 2007